METHODOLOGY OF TEACHING ENGLISH TO CHILDREN OF PRESCHOOL AGE. - JO‘RAYEV BAHODIR ALISHER O‘G‘LI; BALLIYEVA SADOQAT ABULQOSIM QIZI; KAYUMOVA MOHINUR MURODULLAEVNA (TADQIQOTLAR.UZ, 2024)
Abstract: In this article, effective means of teaching English to children of preschool age, and how important English is today, are highlighted.